Memberikan Pengetahuan Tentang Bantuan Hukum Bagi Masyarakat yang Tidak Mampu (Prodeo) - Dina Syaflita; Nurul Hikmah Sinaga; Dinda Aprilia; Sri Wahyuni; Cindy Agusyanti; Dini Julia Putri; Zulaikha Azizah; Yovita Dwi Ananda; Alif Wahid Kamal; Afrido Hidayah (Fakultas Teknik Universitas Cenderawasih, 2022)
This writing contains socialization regarding legal aid which is obtained free of charge which is socialized to the people of Tanjung Rambutan Village.This socialization aims to provide knowledge about the law and also get free legal aid to the underprivileged. The approach method used is a discussion approach with the community regarding legal aid. As for the results of this socialization, the recipient of legal aid is any person or group of poor people who cannot fulfill their basic rights properly and independently. The basic rights in question are the right to food, clothing, health services, education, work and work, and/or housing.